Experimental Investigation of Moisture Removal Rate and Dehumidification Effectiveness of an Internally Cooled Liquid Desiccant Air Dehumidifier (University of Khartoum Engineering Journal, 2022)
Dehumidifier is the most important part in liquid desiccant air conditioning systems. Internally cooled air dehumidifier was found to have better heat and mass transfer performance than the adiabatic one. This paper experimentally studies the performance of an internally cooled dehumidifier using Triethylene Glycol as adesiccant. During the experimental investigation, the dehumidifier inlet parameters, including air flow rate, humidity ratio, temperature, desiccant flow rate, and temperature are varied. The effect of these variables on the moisture condensation rate and dehumidifier effectiveness was studied. It is found that the moisture condensation rate increases with increasing the inlet air flow rate, inlet air humidity ratio, desiccant flow rate, and desiccant solution concentration. While the dehumidifier effectiveness increases with increasing desiccant flow rate andconcentration. The dehumidifier effectiveness decreases with increasing inlet air flow rate and humidity ratios.